Analisis Spasial Aksesibilitas Dan Pelayanan Transportasi Bus Pariwisata Terhadap Objek Wisata Di Kota Medan - Priyono, Eko (Syntax Literate, 2025)
Transportation is a crucial element in supporting the success of urban tourism, particularly in ensuring accessibility and comfort for tourists to tourist attractions. In Medan City, several historical and cultural tourist destinations are still not fully recognized and optimally utilized due to limitations in the tourist transportation system. This study aims to analyze the level of spatial and attributive accessibility of intra-city tourist bus services using a Geographic Information System (GIS) approach. Spatial data in the form of tourist attraction locations, routes, and bus stops were processed using buffering, overlay, and isochrone analysis methods. Meanwhile, attribute data—including operating hours, peak times, and travel time from the city center—were analyzed using a quantitative scoring scheme. The analysis results show that the majority of tourist attractions in Medan are located within a radius of <300 meters from bus stops, have operating hours compatible with bus services, and travel time ≤15 minutes from the city center. All tourist attractions received the highest accessibility index (Scale 3), reflecting excellent spatial-temporal feasibility. These findings support the argument that an integrated land transportation network plays a strategic role in optimizing urban tourism development. This study is expected to serve as a reference in the formulation of spatial data-based tourist transportation policies in urban areas.